Color Doppler Score: A New Approach for Monitoring a Large Placental Chorioangioma. (10th September 2014) - Zoppi, Maria Angelica; Piras, Alessandra; Iuculano, Ambra; Arras, Maurizio; Mulas, Federica; Fadda, Maria Carmela; Cossu, Sergio; Monni, Giovanni
Abstract : We employed color Doppler score as an innovative approach for the prenatal diagnosis and monitoring of a large placental chorioangioma case diagnosed at 26 weeks and the subjective semiquantitative assessment of the vascularization. The blood flow was assessed by a color Doppler score based on the intensity of the color signal with the following value ranges: (1) no flow, (2) minimal flow, (3) moderate flow, and (4) high vascular flow. Weekly examinations were programmed. Initially, a color Doppler score 3 was assigned, remaining unchanged at the following two exams and decreasing to Score 2 in the following 2 exams and to Score 1 thereafter. The ultrasonographic scan showed an increase of the mass size at the second and third exams and was followed by an arrest of the growth persisting for the rest of the pregnancy. Some hyperechogenic spots inside the mass appeared at the end. Expectant management was opted for, and the delivery was at 39, 2 weeks and maternal and fetal outcomes were favourable. The color Doppler score employed for assessment of vascularization in successive examinations proved to be an important tool for the prediction of the chorioangioma involution, and this new approach of monitoring allowed effective surveillance and successful tailored management.